L’Université populaire : une voie d’acculturation émancipatrice pour l’autodidacte ? - Fanette Mathiot (Contextes)
When a worker is self-taught, discovering written culture is a special step in his social mobility path. This article studies the cultural adaptation role played by the working-class Universities in the self-taught workers upward mobility. The interrogation at stake is to know, based upon three literary stories, how emancipatory are working-class Universities at the dawn of the twentieth century. Two fictional stories, Un épisode (1907) by Daniel Halévy and L’Étape (1902) by Paul Bourget, dramatize the failure of working-class Universities, in a realistic perspective for the former, and an ideologic one for the latter. Concerning the autobiographical gesture of Lucien Bourgeois in L’Ascension (1925), it confirms the painful and complex intellectual path of a worker evolving in between two cultures.